Research Trends in the Global South: A Case of Open Access in Sub Sahara Africa - Owango, Joy (My University, 2020)
Presented at #DSGlobal2020 the Digital Science Virtual Event: https://www.digital-science.com/global-showcase-2020/ What are the trends in higher education and research in Sub Sahara Africa What African countries have invested a % of their GDP in higher education and research and what does it mean for the future What African countries have invested in Open Science
Keywords: Sub Sahara Africa; Open Access; Research Trends